Probiotics for the treatment of hyperlipidemia: Focus on gut-liver axis and lipid metabolism - Min You; Li Zhou; Fan Wu; Lei Zhang; Shu-xiu Zhu; Hong-xing Zhang (Pharmacological Research)
Hyperlipidemia, a metabolic disorder marked by dysregulated lipid metabolism, is a key contributor to the onset and progression of various chronic diseases. Maintaining normal lipid metabolism is critical for health, as disruptions lead to dyslipidemia. The gut and liver play central roles in lipid homeostasis, with their bidirectional communication, known as the gut-liver axis, modulated by bile acids (BAs), gut microbiota, and their metabolites. BAs are essential for regulating their own synthesis, lipid metabolism, and anti-inflammatory responses, primarily through the farnesoid X receptor (FXR) and Takeda G protein-coupled receptor 5 (TGR5). Available evidence suggests that high-fat diet-induced the gut microbiota dysbiosis can induce ''leaky gut,'' allowing toxic microbial metabolites to enter the liver via portal circulation, triggering liver inflammation and lipid metabolism disturbances, ultimately leading to hyperlipidemia. Extensive studies have highlighted the roles of probiotics and Traditional Chinese Medicine (TCM) in restoring gut-liver axis balance and modulating lipid metabolism through regulating the levels of lipopolysaccharides, short-chain fatty acids, and BAs. However, the therapeutic potential of probiotics and TCM for hyperlipidemia remains unclear. Here, firstly, we explore the intricate interplay among gut microbiota and metabolites, lipid metabolism, gut-liver axis, and hyperlipidemia. Secondly, we summarize the mechanisms by which probiotics and TCM can alleviate hyperlipidemia by altering the composition of gut microbiota and regulating lipid metabolism via the gut-liver axis. Finally, we emphasize that more clinical trials of probiotics and TCM are necessary to examine their effects on lipid metabolism and hyperlipidemia.